2011
DOI: 10.1111/j.1365-2648.2011.05753.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of actual turnover in a national sample of newly licensed registered nurses employed in hospitals

Abstract: Turnover problems are complex, which means that there is no one solution to decreasing turnover. Multiple points of intervention exist. One specific approach that may improve turnover rates is hospital policies that reduce strains and sprains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
269
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(284 citation statements)
references
References 79 publications
6
269
1
8
Order By: Relevance
“…The notion of "sense of meaning," which leads to greater professional, occupational, or organizational commitment has been identified as an important factor in nurse retention (Brewer, Kovner, Greene, Tukov-Shuser, & Djukic, 2012;Hayes et al, 2006;Jourdain & Chenevert, 2010;Wang, Tao, Ellenbecker, & Liu, 2012). Those who find meaning in their work and have a sense of motivation in the work environment have been shown to have high levels of psychological empowerment, which has been linked to successful practice and increased retention in the NP role (Stewart, McNulty, Griffin, & Fitzpatrick, 2010).…”
Section: Prior Work Experiencementioning
confidence: 99%
“…The notion of "sense of meaning," which leads to greater professional, occupational, or organizational commitment has been identified as an important factor in nurse retention (Brewer, Kovner, Greene, Tukov-Shuser, & Djukic, 2012;Hayes et al, 2006;Jourdain & Chenevert, 2010;Wang, Tao, Ellenbecker, & Liu, 2012). Those who find meaning in their work and have a sense of motivation in the work environment have been shown to have high levels of psychological empowerment, which has been linked to successful practice and increased retention in the NP role (Stewart, McNulty, Griffin, & Fitzpatrick, 2010).…”
Section: Prior Work Experiencementioning
confidence: 99%
“…Previous research by Matsuura, et al (2010) showed that 4.6% of Japanese beginner nurses had resigned from their job within 15 months of practice. Moreover, according to Brewer et al (2012) mentioned that 15% of newlylicensed registered nurses in the USA had changed employers during the 1-year follow-up. In Egypt , at Assuit University Hospital, a study carried out by Abo El-Maged, El-Houfey and Yousef, (2014) revealed that nurses' intention to leave works was higher at ICUs.…”
Section: Introductionmentioning
confidence: 99%
“…The effect and stress caused by disease relapse and common sudden death of patients adds more burdens on the nurses working in such areas and influences their intent to leave [34,35]. Interestingly, it was found that all areas of specialties have an influence on nurses' rate of turnover [12,22]. In another study, with nurses who did not have a choice in place of work, their intent to leave was higher than those who have chosen their working unit [36].…”
Section: Discussionmentioning
confidence: 93%
“…However, these strategies have failed to alleviate the shortage of nurses. This necessitates the focus on retention strategies to keep nurses in their places [11][12][13].…”
Section: Introductionmentioning
confidence: 99%